Detection of multidrug-resistant Salmonella enterica subsp. enterica serovar Typhi isolated from Iraqi subjects - Hamzah Abdulrahman Salman (Veterinary World, 2021)
Background and Aim: Enteric fever initiated by Salmonella enterica subsp. enterica serovar Typhi (S. Typhi) is among the most consistent disease worldwide, particularly in developing countries. The present study aimed to isolate and identify S. Typhi from typhoid suspected patients and determine their antibacterial susceptibility testing.